Measuring the Cost-effectiveness of Various DRM Measures - Toyama, Masato; Sagara, Junko (World Bank, Washington, DC, 2013)
The Japanese experience shows that if done right- preventive investments pay. The Japanese government invested about 7 to 8 percent of the total budget for disaster risk management (DRM) in the 1960s, a move that most probably decreased disaster deaths. Cost-effectiveness analysis (CEA) and cost-benefit analysis (CBA) of DRM projects have been widely implemented both at national and local levels in Japan. Different procedures for such analysis have been followed according to the type of project, the funds, and the governing entity responsible. The Japanese experience shows that CBA is applicable to DRM related projects and is a useful tool in choosing among different options and understanding the effectiveness of a project. This report gives introduction; findings; lessons; and recommendations for developing countries.